KOMPLEKSITAS MODEL BISNIS ADAPTIF BERBASIS TEKNOLOGI DIGITAL DAN JARINGAN BISNIS INTERNASIONAL - Mubarok, Muhammad Husni (MALIA: Journal of Islamic Banking and Finance, 2017)
This paper develops a complexity of adaptive business modelson digital technology and international business network towards a sustainable competitive advantage. Furthermore, this paper aims to integrated the concept of adaptive organizational design with complex business models based on digital technology and and international business network. Adaptive organization design should change consistently with changing technological, ecological, economic, social, digital technology and international business networks.Theoretical basis of the concept of business model and relate it to elements of business model, digital technology and international business network. The complexity of adaptive business models based on digital technology emphasizes the importance of building change, international business networks, developing complex and adaptive organizations for innovation in achieving sustainable competitive advantage. Keywords:complexity,adaptive,technology